STUDY OF BIO-ETHANOL PREPARATION FROM ARENGA PALM SUGAR - Hanny F Sangian; Seni Tongkukut (Sam Ratulangi University, 2011)
STUDY OF BIO-ETHANOL PREPARATION FROM ARENGA PALM SUGAR Hanny F. Sangian1), Seni Tongkukut1) 1) Deptartment of Physics, University of Sam Ratulangi Manado 95115 ABSTRACT This study purposes to prepare bio ethanol by using two column reflux distillation. In North Sulawesi has been known a very potential crop for yielding bio ethanol, is palm crop. Palm crops more productive than cane in yielding sugar and bio fuel per hectare. Its productivity about 4-8 times compared to cane, and its sugar rendement 14%, while cane only 7%. Based on this research were obtained the tapping process should be conducted by unique sequential steps in order to reach pH 8 and brix 12-14% of juice. By using of saccharomyzes ceraviseze and traditional technology was obtained fermented liquor with rate 35–42%. Prior to preparation two column reflux distillation apparatus had been designed and constructed successfully to prepare bio ethanol. Testing of bio ethanol preparation also is carried out by using two column distillation methods. Bio ethanol preparation used beer fermented from palm juice. High purity bio ethanol has been prepared successfully so far at Renewable Energy Lab University of Sam Ratulangi Manado. Surprised results were found that the ethanol purity varied from 95% to 99%. The highest purity is at of 99% by maintaining the column temperature of 78.5oC while purity of 95% is of 78.7oC Keywords: ethanol two column reflux distillation , fermentation, palm juice STUDI PEMBUATAN BIOETANOL DARI NIRA AREN ABSTRAK Studi ini bermaksud untuk membuat bio ethanol dengan menggunakan teknik destilasi dua kolom. Di Sulawesi Utara Indonesia telah dikenal tumbuhan yang dapat menghasilkan bio etanol yang disebut aren (arenga pinnata). Tumbuahan ini adalah lebih produktif menhasilkan gula dari pada tebu dilihat dari jumlah per hektarnya. Produktivitasnya adalah sekitar 4-8 kali dari pada tebu dengan rendemen gulanya sekitar 14%, sementara tebu hanya 7%. Berdasarkan hasil studi diperoleh bahwa proses penyadapan harus dilakukan dengan tahapan yang unik pada pH 8 dan brix 12-14%. Dengan menggunakan saccharomyzes ceraviseze dan teknologi tradisional diperoleh beer dengan kadar 35–42%. Sebelum pembuatan etanol, didahului dengan desain dan konstruksi peralatan destilasi refluks dua kolom. Dari hasil pembuatan didapat hasil yang sangat baik. Bio etanol kemurnian tinggi telah diperoleh dengan sukses selam studi ini. Hasil mengejutkan diperoleh bahwa kemurnian etanol bervariasi dari 95% sampai 99%. Kemurnian tertinggi adalah pada 99%dengan mempertahankan temperatur kolom 78.5oC sementara kemurnian 95% adalah pada 78.7oC. Kata kunci: fermentasi, air nira, etanol, destilasi dua kolom